The formation of person's health: experience of Waldorf school - O.M. Ionova (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
In the article is presented the results of comparative researches of the state of health of Waldorf and traditional schools of students, conducted in different countries (Austria, Holland, Germany, Denmark, Russia, Ukraine, Finland, Switzerland, Sweden). It is set that health saving orientation of Waldorf school brings to the considerable successful results of Waldorf education: Waldorf schoolchildren as compared to the students of traditional schools have the best indexes of physical and psychical health, developed cognitive flairs, personality qualities (individual initiativeness, work, independence of decisions, collaboration with people, social mobility). Due to it among the graduating students of Waldorf schools there almost are not unemployed persons (as well as people with asocial behavior). Among the formers Waldorf students there is a high percent of workers of social, educational and medicine sphere; among them there are many also well-known in the west statesmen, financiers, literati, representatives of art and other.